2003
DOI: 10.1203/01.pdr.0000064581.94126.1c
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Escherichia coli Endotoxin Infusion on the Ventilatory Response to Hypoxia in Unanesthetized Newborn Piglets

Abstract: To determine the effects of endotoxemia on the neonatal ventilatory response to hypoxia, 17 chronically instrumented and unanesthetized newborn piglets (Յ7 d) were studied before and 30 min after the administration of Escherichia coli O55:B5 endotoxin (n ϭ 8) or normal saline (n ϭ 9). Minute ventilation, oxygen consumption, heart rate, arterial blood pressure, and blood gases were measured during normoxia and 10 min of hypoxia (fraction of inspired oxygen, 0.10). Basal ventilation was not modified by E. coli e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
12
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(32 reference statements)
5
12
3
Order By: Relevance
“…In adult humans, endotoxin administration results in changes in the basal respiratory pattern and dyspnea (2). We previously demonstrated that endotoxin infusion in newborn piglets produced attenuation of the VRH (3). In a pilot study, we also observed similar respiratory behavior in 4-to 6-wkold rats.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In adult humans, endotoxin administration results in changes in the basal respiratory pattern and dyspnea (2). We previously demonstrated that endotoxin infusion in newborn piglets produced attenuation of the VRH (3). In a pilot study, we also observed similar respiratory behavior in 4-to 6-wkold rats.…”
supporting
confidence: 71%
“…Respiratory muscle fatigue or alterations in lung mechanics and metabolic rate have been associated with the respiratory changes observed during Gram-positive and negative septicemia in piglets (3,5,6). Particularly, the attenuation in the VRH observed after endotoxin administration to unanesthetized newborn piglets was associated with a significant decrease in VO 2 (3).…”
mentioning
confidence: 99%
“…Indeed, HR fell more quickly in the LPS-treated group at the onset of occlusion, consistent with an enhanced reflex. This finding is in contrast with previous clinical studies of severe sepsis (29,30) and acute LPS injection in animal models (11,23). Similarly, we found no effect of acute on chronic LPS infusion on peripheral vasoconstriction as measured in the femoral vascular bed or on the initial increase in BP, relative to baseline values, in contrast with a previous report of blunted vasoconstriction during occlusion 1 h after LPS injection in the carcass and liver of preterm fetal sheep (12).…”
Section: R801contrasting
confidence: 99%
“…Supporting a direct effect, there is evidence of impaired chemoreflex responses in adult patients with sepsis and multiple organ failure (29,30) and after acute LPS injection in anesthetized adult cats and neonatal piglets (11,23). In contrast, in adult rats there was marked RSNA activation during acute LPS exposure, with no evidence of inhibition of either the baroreflex or chemoreflex (31).…”
mentioning
confidence: 99%
“…In addition, LPS enhances tonic CB chemosensory activity (measured by recording the frequency of chemosensory discharges) but reduces its responsiveness to transient excitatory (hypoxia and nicotine) or depressant (pure oxygen) stimuli. Diminished ventilatory responses to moderate and severe hypoxia in cats reproduces the diminished ventilatory responses to hypoxia observed in unanesthetized newborn piglets subjected to Escherichia coli endotoxin infusion (McDeigan et al, 2003), as well as in rats, in a process that is in part mediated by an inhibitory effect of endothelial nitric oxide on the respiratory control mechanisms (Ladino et al, 2007). Apoptosis studies carried out in CB excised from endotoxemic cats discard that CB diminished chemosensory activity observed in LPS-treated animals resulted from a reduction of functional tissue , and suggest the participation of systemic soluble factors (e.g., cytokines), or locally produced by either resident monocytes/macrophages (Dvorakova et al, 2000), or parenchyma cells.…”
Section: The Arterial Chemoreceptors In Neuroimmunomodulationmentioning
confidence: 68%